Malignancy progression and treatment efficacy estimation of osteosarcoma patients based on in vitro cell culture model and analysis - Hsi-Chieh Lin; Kuei-Hsiang Hsu; Jir-You Wang; Wei-Ming Chen; Yi-Chung Tung; Yu-Ping Su (Journal of the Formosan Medical Association)
Background: Osteosarcoma (OS) usually happens in patients under 20 years old and is notorious for its low survivorship and limb loss. Personalized medicine is a viable approach to increase the efficiency of chemotherapy which is the main prognostic factor for survivorship after surgical treatment. Methods: In this five-year prospective observational study, we collected primary cells of osteosarcoma from 15 patients, and examined the correlation between clinical characters of patients and cell properties characterized using various in vitro assays. The properties including genes expression, pro-angiogenic capability and anti-cancer drug response are characterized respectively by using RT-PCR, tube formation assay, osteogenesis assay and drug testing on 3D tumor spheroid model. Result: The results suggest that OS patients with higher MMP9 expression levels have higher probability to develop skip metastasis (p = 0.041). The 3D tumor spheroid test based on the median lethal dose from 2D culture provides some prognostic value. Patients do not response well to methotrexate (MTX) show higher percentage of high pathology grade (p = 0.009) and lung metastasis (p = 0.044). Also, patients respond well to ifosfamide (IFO) have higher probability to achieve high tumor necrosis rate (p = 0.007). Conclusion: The association between cell properties and clinical characters of patients provided by our data can act as potential prognostic factors to help physicians to develop effective personalized chemotherapy for osteosarcoma treatments.